PENGARUH PEMBERIAN PUPUK BOKASHI DAN PUPUK UREA TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN SAWI (Brassica juncea L.) - Alfhons ' Pangaribuan; Armaini ' '; Edison ' Anom (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
ABSTRACT The research purpose to observe the influence of a combination of bokashi fertilizer and urea fertilizer, and knowing dosage bokashi and urea for the growth and the production of plants mustard greens (Brassica Juncea L). The reaserch has implemented in the garden faculty the farm university of Riau in campus Bina Widya KM 12,5 Village Simpang Baru District Tampan Pekanbaru. The research has implented for 2 months was counted started April 2016 to Mey 2016. The study was carried out experiments using a Completely Randomized Design (CRD) factorial consting of 2 factors, the first factor is bokashi fertilizer (B) consist of 3 level and the second factor is urea fertilizer consist of 2 level, so in the can 6 a combination of treatment each 4 repetition, so obtained 24 plot. Each plot consist of 25 plants and taken 5 plants as sample. Parameters observed is high plants (cm), sum leaves (sheet) broad leaves (cm2), volume the root (ml) and the weight of fresh plants (g). Data obtained from the results of reasearch analyzed statistically with kind of a variety and proceed with further test (DNMRT) on the level 5%. Based on the results of reseach influence of giving bokashi fertilizer and urea fertilizer against the growth and the production of plants mustard greens (Brassica Juncea L) give the influence of a real in the parameters broad leaves and the weight of fresh plants. Based on the results of research obtained the results of the best on the giving bokashi fertilizer with a dosage of 2 tons/ha and dosage urea fertilizer 150 kg/ha so it can be advised to do fertilization to dosage on plants mustard greens. Keyword: Mustard Greens, Bokashi Fertilizer and Urea Fertilizer